Is aggregate demand wage-led or profit-led? National and global effects - Onaran, Özlem; Galanis,Giorgos (Geneva, 2012)
"This paper estimates the effects of a change in the wage share on growth in the G20 countries using a post-Keynesian/post-Kaleckian model, analyses the interactions among different economies, and calculates the global multiplier effects of a simultaneous decline in the wage share."